Should higher education institutions worry about the precarisation of professional work? - Pavlin, Samo (Annales. Series historia et sociologia, 2018)
This conceptual paper seeks to show why and in what ways higher education should worry about the precarisation of professional work. Increasing number of higher education institutions recently strive to improve professional relevance of study programmes in relation to skill (mis)matches and the problem of unemployment. In this context the paper examines the key factors of the development of professional workers in higher education and explains the precarisation of professional work as an increasingly relevant social problem. Particular attention is paid to comparing the precarisation of young graduates of higher education with the elements of precarisation of academics. The paper concludes that the precarisation of graduates and the quality of academic employment are related phenomena.
Keywords: College graduates; Diplomanti (univerze in visoke šole); Labor market; Precarious employment; Prekarno delo; Profesionalizacija; Professionalization; Trg dela